RESEARCH ON THE THICK COMPOSITE LAMINATE BOLT JOINT STRENGTH - LIU Tong; XU XiWu; LIN ZhiYu (Jixie qiangdu)
A 3D model of composite laminates with bolted joint is created by using the software ABAQUS. By introducing the 3D Hashin failure criteria and considering the tightening torque,the partition and the global degradation models were established. With this method,the failure process and the linking strength of single-lap,single-bolt joints were calculated. The results shows that the load-displacement curve by using global degradation model doesn’t degrade enough and the computing results are more accurate by using the partition degradation model. With the increase of thickness,the linking strength of bolted single-lap composite joints decrease all the time and the speed of degradation gets slower and slower. It means that with the increase of thickness,the lifting bearing capacity of structure reduces. It also indicates that the ultimate strength of laminate is enhanced with appropriate tightening torque and excessive tightening torque impairs the load carrying capacity of the structure.